Literature Review: Application of Contextual Teaching and Learning Model to Improve Learning Interest of Elementary School Students - Adelia, Erika (International Journal of Students Education, 2024)
This study discusses the application of the Contextual Teaching and Learning (CTL) model in an effort to increase students' interest in learning in elementary schools. Education is not only aimed at transferring knowledge, but also at forming character and life skills. However, conventional methods that are often used in the learning process cause students to act as passive listeners, thus reducing their involvement and interest. The CTL model Contextual Teaching and Learning (CTL), which emphasizes active student involvement and relates learning materials to real situations, is considered effective in overcoming this problem. This study uses a literature review method to evaluate the effects of implementing Contextual Teaching and Learning (CTL) for the past five years. The results of the analysis show that the model Contextual Teaching and Learning (CTL) can significantly increase students' interest in learning by encouraging them to actively participate and find solutions independently. In addition, this study also identified several advantages and disadvantages of the Contextual Teaching and Learning (CTL) model, and showed its impact on students' discussion skills and learning outcomes. Thus, it is expected that the application of the model Contextual Teaching and Learning (CTL) can improve the quality of education at the elementary school level, creating a more interactive and enjoyable learning atmosphere.